Effects of reaction temperature, time and particle size on switchgrass microwave pyrolysis and reaction kinetics - Zhou, Rui; Lei, Hanwu; Julson, James L. (International Journal of Agricultural and Biological Engineering, 2013)
This study investigated microwave pyrolysis of switchgrass with particle sizes from 0.5 mm to 4 mm and determined the effects of reaction temperature and time on the yields of bio-oil, syngas, and bio-char. A prediction model was satisfactorily developed to describe the bio-oil conversion yield as a function of reaction temperature and time. Second-order reaction kinetics was also developed to model the switchgrass pyrolysis. Switchgrass with different particle sizes was found to be similarly pyrolyzed by microwave heating. The research results indicated that thermochemical conversion reactions can take place rapidly in large-sized switchgrass by using microwave pyrolysis. GC-MS analysis indicates that the bio-oil contained a series of important and useful chemical compounds: Phenols, aliphatic hydrocarbons, aromatic hydrocarbons, and furan derivatives. These chemical compounds evolved were related to the pyrolysis conditions.